Reducing the need for carbon dioxide monitoring in the investigation of paediatric sleep disordered breathing. Issue 4 (4th October 2018) - Trucco, Federica; Bush, Andrew; Tan, Hui-Leng
There is increasing interest in the use of home sleep studies to diagnose paediatric sleep disordered breathing (SDB) as they are potentially more cost-effective, convenient and representative of the child's typical nights' sleep [1–3]. One concern is that most home sleep study equipment does not include measurement of carbon dioxide. Overnight cardiorespiratory polygraphy without CO2 monitoring is adequate in children investigated for uncomplicated obstructive sleep apnoea http://ow.ly/P7Fs30lpKFj